Assessment of phage-mediated control of antibiotic-resistant Salmonella Typhimurium during the transition from planktonic to biofilm cells. (January 2022) - Dawan, Jirapat; Ahn, Juhee
Abstract: This study was designed to evaluate the abilities of phage P22 to lyse, eradiate, and disperse the biofilm cells of Salmonella enterica serovar Typhimurium ATCC 19585 (ST WT ), ciprofloxacin-induced Typhimurium ATCC 19585 (ST CIP ), S . Typhimurium KCCM 40253 (ST KCCM ), and multidrug-resistant S . Typhimurium CCARM 8009 (ST CCARM ) in association with hydrophobicity, auto-aggregation, motility, protein content, extracellular DNA, and depolymerase activity. The affinity to hexadecane was significantly increased in ST WT, ST KCCM, and ST CCARM cells after P22 infection. All strains tested showed relatively higher auto-aggregation abilities in the presence of P22 than the absence of P22. ST KCCM showed the greatest auto-aggregative ability (23%) in the presence of P22, while ST WT showed the least auto-aggregative ability (9%) in the absence of P22. The bacterial swimming motility affected the bacterial attachment at the early stage of biofilm formation. The red, dry and rough morphotype was observed for all strains tested. The numbers of ST WT, ST CIP, and ST KCCM planktonic cells were considerably reduced by 7.2, 5.0, and 5.0 log CFU/ml, respectively, and ST WT, ST CIP, and ST KCCM biofilm-forming cells were reduced by 5.8, 4.5, and 4.9 log, respectively, after 24 h of phage infection. The depolymerase produced by phages were confirmed by the presence of outer rim of plaques. Phages could be considered as promising alternatives for the control of biofilms due to their advantages including enzymatic degradation of extracellular biofilm matrix. The study would provide useful information for understanding the dynamic interactions between phages and biofilms and also designing the effective phage-based control system as an alterative strategy against biofilms. Highlights: The lytic activity of P22 against Salmonella planktonic cells was highly correlated to the biofilm forming ability. The phage P22 was effectively inhibited the biofilm-forming ability of Salmonella planktonic cells. The P22-derived depolymerase enhanced the lytic activity against preformed biofilm cells.